Pattern Recognition and Machine Intelligence 5th International Conference, PReMI 2013, Kolkata, India, December 10-14, 2013. Proceedings - Maji, Pradipta.; Ghosh, Ashish.; Murty, M. Narasimha.; Ghosh, Kuntal.; Pal, Sankar K. (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 5th International Conference on Pattern Recognition and Machine Intelligence, PReMI 2013, held in Kolkata, India in December 2013. The 101 revised papers presented together with 9 invited talks were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on pattern recognition; machine learning; image processing; speech and video processing; medical imaging; document image processing; soft computing; bioinformatics and computational biology; and social media mining.